(untitled) (Progress Annals: Journal of Progressive Research, 2024)
This article focuses on developing the future technology teacher’s professional competence in the process of extracurricular activities, raising a spiritually morally mature, independent worldview, a creative thinker, a rich national heritage, as well as a harmonious personality devoted to Universal and national values